Comparison of high‐ and low‐frequency fatigue properties of structural steels S355J0 and S355J2 - Klusák, Jan; Horník, Vít; Lesiuk, Grzegorz; Seitl, Stanislav (Fatigue & fracture of engineering materials & structures, 2021)
The paper brings results of high‐cycle fatigue and very‐high‐cycle fatigue tests of the steel S355 tested during low‐ and high‐frequency loading. Two grades of structural steel (S355J0 and S355J2) were tested to gain fatigue properties that serve as inputs to reliable finite element calculations of cyclically loaded structures. Experimental measurements of both steel grades were performed on low‐frequency hydraulic and high‐frequency ultrasonic fatigue testing systems. Both low‐ and high‐frequency loading showed higher lifetime for the grade S355J2. The difference between the two studied steel grades was more apparent during low‐frequency loading. The significant difference between the results of low‐ and high‐frequency loading tests can be explained by the fact that the resistance to plastic deformation increases with an increasing rate of deformation. Fracture surfaces were studied by electron microscopy, where they exhibited both surface and internal crack initiation. Highlights The fatigue life of the studied steels exhibited strong dependence on loading frequency. The life under fatigue ultrasonic loading is much higher than the life under low frequency. The purity of the S355 steels has a significant impact on their fatigue life. The fatigue life of the steels S355J0 and S355J2 is in correlation to their ultimate strength.